2014
DOI: 10.12659/msm.890433
|View full text |Cite
|
Sign up to set email alerts
|

Primary orbital tumors: A review of 122 cases during a 23-year period: A histo-clinical study in material from the ENT Department of the Medical University of Silesia

Abstract: BackgroundThe aim of this study was to investigate the distribution of different types of primary orbital tumors, histopathological diagnosis, and postoperative complications.Material/MethodsWe analyzed 122 patients (68 women and 54 men) with orbital tumors, hospitalized in the ENT Department of the Medical University of Silesia in Katowice during 1990–2013. The patients were characterized in terms of anatomic, topographical, histopathological, and clinical parameters. The role of diagnostic imagining such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Markowski et al . [ 30 ] divided the site of the tumors into four areas: upper lateral, upper medial, lower lateral, and lower medial on the basis of image studies. Boari et al .…”
Section: Discussionmentioning
confidence: 99%
“…Markowski et al . [ 30 ] divided the site of the tumors into four areas: upper lateral, upper medial, lower lateral, and lower medial on the basis of image studies. Boari et al .…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported by Demirci et al [ 7 ] who found that the most common clinical features at presentation were a periorbital palpable mass (26%), followed by proptosis (18%) and pain (15%). Markowski et al [ 22 ] found that the most frequent manifestations were proptosis in 100% of patients, eyelid swelling in 54%, limitation of eye movement in 45%, decreased visual acuity in 43%, pain in 30%, and diplopia in 16%. In our series, we observed that most of the lymphoproliferative lesions were in the anterior orbit (extraconal) while the majority of the vascular and neurogenic lesions arose intraconally.…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors, the most common primary malignant orbital tumour is Lymphoma malignum followed by melanoma malignum, carcinoma anaplasticum, carcinoma planoepitheliale, adenocarcinoma, and tumour mixtus malignus. Malignant lymphoma was detected in 11.47% of patients [51].…”
Section: Primary Orbital Tumoursmentioning
confidence: 99%
“…Orbital tumours are divided into primary tumours arising from orbital tissues, tumours penetrating the orbital cavity from surrounding tissues, and metastases from other parts of the body. The main symptom is exophthalmos, reduction of eye movement with or without double vision, swelling and redness of the eyelids, and conjunctiva [50,51].…”
Section: Eye-setting Abnormalities (Unilateral or Bilateral Exophthal...mentioning
confidence: 99%
See 1 more Smart Citation